Assessment of Antinuclear Antibody (ANA) Levels in Patients from Al-Bayda, Libya (Comprehensive Journal of Science, 2025)
This cross-sectional study aimed to determine the prevalence and distribution ofantinuclear antibody (ANA) levels among patients referred for laboratory testing at aspecialized medical laboratory in Al-Bayda, Libya, during 2024-2025. A retrospectiveanalysis of 244 patient records was conducted, examining age, sex, test year, and ANA results(categorized as normal or elevated). The findings revealed that the overwhelming majority oftested individuals (92.2%) exhibited ANA levels within normal reference ranges, while only asmall subset (7.8%) showed elevated levels. The study population demonstrated a mean ageof 42.3 years with a notable female predominance (71.7%). Among the 19 positive cases,females showed higher positivity rates (9.1%) compared to males (4.3%), and individualsaged ≥40 years constituted 63% of positive results. However, statistical analysis indicated nosignificant associations between ANA positivity and sex (χ² = 2.15, p = 0.14) or age (t = 1.32,p = 0.19). The observed ANA positivity rate (7.8%) was notably lower than rates reportedfrom other Libyan cities (9-11%) and international benchmarks. These findings highlight theneed for expanded multicenter studies across Libya to better understand regional variations inautoimmune disease prevalence and improve diagnostic capabilities
Keywords: Antinuclear Antibody (ANA) ،Autoimmune Diseases ،Prevalence، Libya ،Indirect Immunofluorescence Assay (IFA) ،Demographic Factors، Seroprevalence